Challenges and Opportunities From COVID-19 vis-à-vis Informal Cross-Border Women Entrepreneurs Scenario in Zimbabwe - Mufaro Dzingirai; Munyaradzi Chagwesha; Florence Mudzurandende (IGI Global, 2022)
Although entrepreneurship is widely accepted as a driver of economic development and growth across the globe, the COVID-19 pandemic and several lockdowns have created a unique situation in the entrepreneurship discourse. Accordingly, this chapter aims at providing empirical evidence on the challenges and opportunities emanating from COVID-19 within the context of informal cross-border women entrepreneurs. This study establishes five challenges, namely, business closures, caregiving responsibility, the decline in demand, shortage of goods, and liquidity crisis. Moreover, it also establishes digital marketing and business networks as opportunities. The recommendations to deal with these challenges are proffered and the suggestions for further study are captured.